Relics of eclogite facies assemblages in the Ceara Central Domain, NW Borborema Province, NE Brazil: Implications for the assembly of West Gondwana - (:unkn) unknown (My University, 2009)
The Borborema Province, in the NE of Brazil, is a rather complex piece in the Brazil-Africa puzzle as it represents the junction of the Dahomeyide/Pharusian, Central African, Aracuai and Brasilia fold belts located between the West-African/Sao Luis, Congo/Sao Francisco and Amazonas craton. The correlation between the Dahomeyides from W-Africa (Ghana, Benin, Togo, and Mali) and the Borborema Province involves the Medio Coreau and Central Ceara domains. The inferred continuation of the main oceanic suture zone exposed in the Dahomeyides of W Africa is buried beneath the Phanerozoic Parnaiba Basin in Brazil (northwest of the Medio Coreau domain) where some high density gravity anomalies may represent hidden remnants of an oceanic suture. In addition to this major suture a narrow, nearly continuous strip composed of mainly mafic pods containing relics of eclogite-facies assemblages associated with partially migmatized granulite-facies metapelitic gneisses has been found further east in the NW Borborema Province. These high pressure mafic rocks, interpreted as retrograded eclogites, are located between the Transbrasiliano Lineament and the Santa Quiteria continental arc and comprise primitive to evolved arc-related rocks with either arc- or MORB-type imprints that can indicate either deep subduction of oceanic lithosphere or roots of continental and oceanic magmatic arcs. Average peak P-T conditions under eclogite-facies metamorphism (T=770 degrees C and P = 17.3 kbar) were estimated using garnet-clinopyroxene thermometry and Jd content in clinopyroxene. Transition to granulite-facies conditions, as well as later widespread re-equilibration under amphibolite facies, were registered both in the basic and the metapelitic rocks and suggest a clockwise P-T path characterized by an increase in temperature followed by strong decompression. A phenomenon possibly related to the exhumation of a highly thickened crust associated with the suturing of the Medio Coreau
Keywords: African Research